THE SOULMATE EQUATION - Lauren, Christina (Piatkus, An imprint of Little, Brown Book Group, 2021)
Jess is a numbers genius, but when it comes to love she's had to accept there is no magic formula. Juggling a career with raising her daughter, it's not surprising that her love life is. . . non-existent. When yet another date ends in disaster, she's prepared to give up on love for good. But then she hears about a buzzy new matchmaking company that claims to find you the One using a DNA equation. Suddenly, love doesn't seem quite so far out of reach . . .Until her test shows an unheard-of 98% compatibility with the company's founder, Dr River Pena. Jess already knows Dr Pena, and this man is 100% not her soulmate. Yet as the pair are dragged from one event to the next as the ultimate 'Diamond' pairing, Jess begins to realise that there might be more to the scientist - and to the science behind a soulmate - than she thought.